PER1, GUP1 and CWH43 of methylotrophic yeast Ogataea minuta are involved in cell wall integrity. Issue 2 (29th November 2017) - Xu, Xin‐Xin; Komatsuzaki, Akiko; Chiba, Yasunori; Gao, Xiao‐Dong; Yoko‐o, Takehiko
Abstract: In eukaryotes, the glycosylphosphatidylinositol (GPI) modification of many glycoproteins on the cell surface is highly conserved. The lipid moieties of GPI‐anchored proteins undergo remodelling processes during their maturation. To date, the products of the PER1, GUP1 and CWH43 genes of the yeast Saccharomyces cerevisiae have been shown to be involved in the lipid remodelling. Here, we focus on the putative GPI remodelling pathway in the methylotrophic yeast Ogataea minuta . We found that the O. minuta homologues of PER1, GUP1 and CWH43 are functionally compatible with those of S. cerevisiae . Disruption of GUP1 or CWH43 in O. minuta caused a growth defect under non‐permissive conditions. The O. minuta per1 Δ mutant exhibited a more fragile phenotype than the gup1 Δ or cwh43 Δ mutants. To address the role of GPI modification in O. minuta, we assessed the effect of these mutations on the processing and localization of the O. minuta homologues of the Gas1 protein; in S. cerevisiae, Gas1p is an abundant and well‐characterized GPI‐anchored protein. We found that O. minuta possesses two copies of the GAS1 gene, which we designate GAS1A and GAS1B . Microscopy and western blotting analysis showed mislocalization and/or lower retention of Gas1Ap and Gas1Bp within the membrane fraction in per1 Δ or gup1 Δ mutant cells, suggesting the significance of lipid remodelling for GPI‐anchored proteins in O. minuta . Localization behaviour of Gas1Bp differed from that of Gas1Ap. Our data reveals, for the first time (to our knowledge), the existence of genes related to GPI anchor remodelling in O. minuta cells.